Single‐Leg Squat Performance is Impaired 1 to 2 Years After Hip Arthroscopy. Issue 4 (27th July 2015) - Charlton, Paula C.; Bryant, Adam L.; Kemp, Joanne L.; Clark, Ross A.; Crossley, Kay M.; Collins, Natalie J.
Abstract: Objective: To evaluate single‐leg squat performance 1‐2 years after arthroscopy for intra‐articular hip pathology compared with control subjects and the nonsurgical limb, and to investigate whether single‐leg squat performance on the operated limb was associated with hip muscle strength. Design: Cross‐sectional study. Setting: Private physiotherapy clinic and university laboratory. Participants: Thirty‐four participants (17 women, 36.7 ± 12.6 years) 1‐2 years after hip arthroscopy and 34 gender‐matched control subjects (17 women, 33.1 ± 11.9 years). Methods: Participants performed single‐leg squats using a standardized testing procedure. Squat performance was captured using video. Video footage was uploaded and reformatted for analyses. Hip muscle strength was measured with handheld dynamometry using reliable methods. Outcome Measures: Frontal plane pelvic obliquity, hip adduction, and knee valgus were measured. Repeated measures analysis of variance evaluated between‐group differences, with limb as a within‐subjects factor (surgical versus nonsurgical) and gender as a between‐subjects factor ( P < .05). Results: The hip arthroscopy group demonstrated significantly greater apparent hip adduction (mean difference 2.7°, 95% confidence interval [CI] 0.7°‐4.8°) and apparent knee valgus (4.0°, 95% CI 1.0°‐7.1°) at peak squat depth compared with control subjects. The operated limb also demonstrated significantly greater pelvic obliquity during single‐leg stance compared with the nonsurgical limb (1.2°, 95% CI 0.1°‐2.3°). Women had significantly greater apparent hip adduction (standing 1.6°, 95% CI 0.5°‐2.6°; peak squat depth 2.4°, 95% CI 0.3°‐4.4°) and apparent knee valgus (standing 3.3°, 95% CI 1.8°‐4.7°; peak squat depth 3.1°, 95% CI 0°‐6.1°). Significant positive correlations were found between frontal plane angles and hip flexor and extensor peak torque ( P > .05). Conclusion: One to 2 years after hip arthroscopy, deficits in single‐leg squat performance exist that have the potential to increase hip joint impingement and perpetuate postoperative symptoms. Rehabilitation after hip arthroscopy should target retraining in functional single‐leg positions.